Efficacy, perception, and utilization of pediatric teledermatology: A systematic reviewCapsule Summary - Joshua Burshtein, MD; Maria Gnarra Buethe, MD, PhD; Mondana H. Ghias, MD; Amy Buros Stein, PhD; Sharon Glick, MD; Shoshana Marmon, MD, PhD (Elsevier, 2023)
Background: The use of teledermatology abruptly expanded with the arrival of COVID-19. Here, we review recent studies regarding the efficacy, perception, and utilization of telemedicine in the pediatric population. Objective: To evaluate the current state of pediatric teledermatology. Methods: A literature search was performed using the terms "pediatric," "teledermatology," "dermatology," "telemedicine" and "telehealth" in PubMed, Scopus, Embase, and Google Scholar. 44 articles published between 2008 and 2022 were included. Results: Diagnostic concordance between pediatric teledermatologist and in-person dermatologist ranged from 70.1% to 89%. Conditions treated with pediatric teledermatology were similar to those treated in-person. The rate of in-person follow-up after an initial telemedicine appointment pre and postpandemic was 12% to 51.9% and 13.5% to 28.1%, respectively. Patient satisfaction with teledermatology was between 70% to 98% and provider satisfaction was approximately 95%. The integration of teledermatology can reduce missed appointments and wait times among pediatric patients. However, considerable technological challenges exist, particularly in underserved communities. Globally, teledermatology may expand access to care though limited literature exists regarding its use in pediatric populations. Conclusion: Telemedicine is effective for the diagnosis and treatment of many dermatological conditions in children, with high patient and provider satisfaction. Implementation of teledermatology can potentially increase access to care both locally and globally, but obstacles to engagement remain.